2022
DOI: 10.48101/ujms.v127.8500
|View full text |Cite
|
Sign up to set email alerts
|

The impact of splenectomy on human lipid metabolism

Abstract: Background: Splenectomy impacts hematological, immunological, and metabolic functions of the patient. Since our understanding of its metabolic effects, in particular effects on lipid metabolism, is limited, this study aims to investigate the effects of splenectomy on lipid metabolism. Methods: The data from 316 patients undergoing splenectomy between 2009 and 2019 were retrospectively analyzed. Thirty-eight patients whose serum lipid values were measured both preoperatively and 1 year after surgery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The crucial role in systemic lipid regulation of the spleen was also reported by Alberti et al, who found that splenectomy is associated with changes in lipid metabolism by an elevation of total cholesterol and low-density lipoprotein (LDL) levels while decreasing high-density lipoprotein (HDL) levels [68]. The alteration of LDL cholesterol due to the splenectomy was also observed by other authors [11,12], who linked this operation with the onset of atherosclerosis and other cardiovascular diseases. Wysocki et al observed that in splenectomized patients, triglyceride (TG) levels are significantly higher, while in cases of splenomegaly, total cholesterol (TC) and LDL are notably decreased [69].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The crucial role in systemic lipid regulation of the spleen was also reported by Alberti et al, who found that splenectomy is associated with changes in lipid metabolism by an elevation of total cholesterol and low-density lipoprotein (LDL) levels while decreasing high-density lipoprotein (HDL) levels [68]. The alteration of LDL cholesterol due to the splenectomy was also observed by other authors [11,12], who linked this operation with the onset of atherosclerosis and other cardiovascular diseases. Wysocki et al observed that in splenectomized patients, triglyceride (TG) levels are significantly higher, while in cases of splenomegaly, total cholesterol (TC) and LDL are notably decreased [69].…”
Section: Discussionsupporting
confidence: 52%
“…It acts as a reservoir for lipids; macrophages store fat through phagocytosis and the spleen exerts the LPL activity. Due to those reasons, splenectomy appeared to have a negative impact on lipid metabolism [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Crude fat originating from BD (i.e., the meadow hay and concentrate). 8 Total crude fat originating from the BD and added oils (i.e., rapeseed oil (R-O) and fish oil (F-O)). 9 Total gross energy of the BD enriched in R-O and F-O without or with antioxidant(s) (i.e., CA, Se as yeast rich in seleno-methionine (Se Ye ) or Se 6 (Se as sodium selenate)).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a splenic connection with the propagation of certain diseases connected with lipid disorders (like Niemann-Pick’s disease, Gaucher’s disease, Fabry disease or gangliosidoses) was also reported [ 6 ]. Total splenectomy may unfavorably affect levels of plasma lipids (triglycerides, cholesterols, fatty acids (FA)), and lipoproteins [ 7 , 8 ] and thus lead to the development of atherosclerosis and other cardiovascular disorders. The influence of the spleen in lipid metabolism was confirmed in rat, rabbit, and dog models [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%